Designing a Digital Guest Book Information System Using the Waterfall Method to Improve Visit Management Efficiency - Muhammad, Andhika Fairuz; Chotijah, Umi (Bahasa Indonesia, 2025)
Visitor management at PT Swabina Gatra Travel still relies on a manual paper-based system, which hinders operational efficiency. This conventional recording is prone to errors, data loss, and is time-consuming, especially during the recapitulation process for management. These weaknesses directly affect the speed of service and the accuracy of visit information. This study aims to design and implement a web-based digital guest book information system at PT Swabina Gatra Travel to automate data recording and enhance visit management efficiency. The Waterfall Method was used for development due to its systematic, linear, and structured workflow, suitable for projects with stable, defined requirements. The system is designed with digital guest data input features, a monitoring dashboard, and automated report generation. Implementation results show that the system is proven to reduce queuing time and facilitate instant data access, which is a significant improvement compared to the manual system. This study concludes that the implementation of the digital guest book using the Waterfall method successfully modernizes visit administration at PT Swabina Gatra Travel and improves operational efficiency.